Outer Membrane Vesicles from Brucella abortus Promote Bacterial Internalization by Human Monocytes and Modulate Their Innate Immune Response - Pollak, Cora Noemí (2012)
Outer membrane vesicles (OMVs) released by some Gram-negative bacteria have been shown to exert immunomodulatory effects that favor the establishment of the infection. The aim of the present study was to assess the interaction of OMVs from Brucella abortus with human epithelial cells (HeLa) and monocytes (THP-1), and the potential immunomodulatory effects they may exert. Using confocal microscopy and flow cytometry, FITC-labeled OMVs were shown to be internalized by both cell types. Internalization was shown to be partially mediated by clathrin-mediated endocytosis. Pretreatment of THP-1 cells with Brucella OMVs inhibited some cytokine responses (TNF-α and IL-8) to E. coli LPS, Pam3Cys or flagellin (TLR4, TLR2 and TLR5 agonists, respectively). Similarly, pretreatment with Brucella OMVs inhibited the cytokine response of THP-1 cells to B. abortus infection. Treatment of THP-1 cells with OMVs during IFN-γ stimulation reduced significantly the inducing effect of this cytokine on MHC-II expression. OMVs induced a dose-dependent increase of ICAM-1 expression on THP-1 cells and an increased adhesion of these cells to human endothelial cells. The addition of OMVs to THP-1 cultures before the incubation with live B. abortus resulted in increased numbers of adhered and internalized bacteria as compared to cells not treated with OMVs. Overall, these results suggest that OMVs from B. abortus exert cellular effects that promote the internalization of these bacteria by human monocytes, but also downregulate the innate immune response of these cells to Brucella infection. These effects may favor the persistence of Brucella within host cells.